Loneliness as a risk factor for care home admission in the English Longitudinal Study of Ageing. (10th July 2018) - Hanratty, Barbara; Stow, Daniel; Collingridge Moore, Danni; Valtorta, Nicole K; Matthews, Fiona
Abstract: Background: loneliness has an adverse effect on health and well-being, and is common at older ages. Evidence that it is a risk factor for care home admission is sparse. Objective: to investigate the association between loneliness and care home admission. Setting: English Longitudinal Study of Ageing (ELSA). Participants: two-hundred fifty-four individuals across seven waves (2002–15) of ELSA who moved into care homes were age, sex matched to four randomly selected individuals who remained in the community. Methods: logistic regression models examined associations between loneliness, socio-demographic factors, functional status and health on moving into care homes. Results: loneliness (measured by the University of California, Los Angeles (UCLA) Loneliness Scale and a single-item question from the Center for Epidemiological Studies Depression Scale (CES-D)) was associated with moving into a care home (CES-D OR 2.13, 95% CI 1.43–3.17, P = 0.0002, UCLA OR 1.81, 95% CI 1.01–3.27, P = 0.05). The association persisted after adjusting for established predictors (age, sex, social isolation, depression, memory problems including diagnosis of Alzheimer's disease, disability, long-term physical health and wealth). The impact of loneliness (measured by CES-D) on admission accounted for a population attributable fraction of 19.9% (95% CI 7.8–30.4%). Conclusions: loneliness conveys an independent risk of care home admission that, unlike other risk factors, may be amenable to modification. Tackling loneliness amongst older adults may be a way of enhancing wellbeing and delaying or reducing the demand for institutional care.